A spray gun - Aris, Ishak; Iqbal, A. K. M. Parvez (2011)
The present invention comprising two spray units (100) and a casing (500), a holding assembly (103) with a shaft (105), a triggering lever (401), an air control unit (200), a linear motor (301) and a motor driver (303). The present invention provides a spray gun that can operate as an air spray gun, a high volume low pressure (HVLP) air spray gun, an airless spray gun and an air assisted airless spray gun without dismantling the total system. The air control system (200) is configured in such a way that it can be supplied required amount of air as desired. A sensor-less DC linear motor (301) is used to trigger the spray gun instead of using pneumatic system.